PENINGKATAN PENGETAHUAN PENDEWASAAN USIA PERKAWINAN PADA REMAJA DI SMAN 2 MUKOMUKO - maiseptyasari, ruri; Ningsih, Dewi Aprilia; Apriani, Waytherlis (Poltekkes Kemenkes Bengkulu, 2022)
Data from the World Health Organization (WHO) shows that 16 million births occur to mothers aged 15-19 years or 11% of all births in the world, the majority (95%) occurring in developing countries (Sariani, 2020). The practice of early marriage in the world is most prevalent in Africa and Southeast Asia. In Southeast Asia, data shows that around 10 million children under the age of 18 are married, while in Africa it is estimated that 42% of the child population, married before they were 18 years old. In general, child marriage is more common in girls than boys, about 5% of boys marry before they are 19 years old. In addition, it was also found that women were three times more likely to marry early than men. The purpose of this community service is to increase the knowledge of adolescents about maturing age at marriage. The target of this community service is 40 teenagers of SMAN 2 Mukomuko. This service begins with the provision of a pre-test questionnaire, then conducts counseling and then administers a post-test questionnaire.